2006
DOI: 10.1007/s11547-006-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Studio dinamico della deglutizione e dose radiante al paziente

Abstract: With the defined radiological procedure, the obtained KAP values are lower than recorded doses in interventional radiology, and the corresponding values of entrance skin dose are lower than the threshold dose for deterministic effects. Considering the effective dose at the median KAP value, the probability for stochastic effects is shown to be low, at approximately 1 in 39,000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
2
7
0
1
Order By: Relevance
“…Table 2 summarizes MBSS fluoroscopy exposure times reported in the ten identified published studies [1017, 2123]. Overall, average radiation exposure time using MBSImP©™ was 2.9 min with a 95% confidence interval of 2.8 to 3.0 min (range = 0.4 to 8.0 min), well within the range of exposure times reported in the literature.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Table 2 summarizes MBSS fluoroscopy exposure times reported in the ten identified published studies [1017, 2123]. Overall, average radiation exposure time using MBSImP©™ was 2.9 min with a 95% confidence interval of 2.8 to 3.0 min (range = 0.4 to 8.0 min), well within the range of exposure times reported in the literature.…”
Section: Resultssupporting
confidence: 52%
“…From interviewing the novice clinicians, we learned that their standardized training in swallowing physiology and impairment and using a standardized protocol increased their confidence and efficiency in execution of the exam. Interpolating from Moro’s results, an increase in fluoroscopy time of 12 sec relates to an increase of between 0.024 and 0.036 mSv [10]. While this related increase in radiation dose is small, according to the linear, no-threshold dose response for assessing stochastic effects of radiation exposure and the “As Low As Reasonably Achievable” (ALARA) principle, even small increases in radiation exposure are meaningful [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our case was given speech therapy too. And instruction and exercise therapy of the positioning that, in addition, was appropriate were provided in addition, and a deglutition function improved it.It is reported that VE and VF is useful for a deglutition usability test [12,13]. In our case, we could confirm the paralytic pattern and deglutition situation in VE, VF, and there was training without pneumonia being caused.…”
supporting
confidence: 71%